An examination of the dynamic feature of WTC through dyadic group interaction. (December 2015) - Yu, Miao
Abstract: Willingness to Communicate (WTC) is a construct which has been consistently conceived as under the convergent influences of psychological, personal, and social, as well as communicative variables. However, few studies have considered WTC's dynamic feature in a situated language learning context. The present study does so by examining how the fluctuation of WTC influences language learners' actual language use when the interlocutor set-ups are altered based on their matched or mismatched WTC level. The language learners' language use is quantified as their actual language output in communication tasks, including the number of words and the amount of turn-taking produced in the discourse. It was found that the communication output of language learners with low WTC did not improve when they were paired up with peers of higher WTC. The changes in communication behaviors of low WTC individuals when they worked together with interlocutors of different WTC levels suggest that WTC is dynamic, and is jointly constructed by the interlocutors during a communication task.